The role of laparoscopy in perforated peptic ulcer: a comment on the Australian cohort study - Guadagni, Simone; Furbetta, Niccolò; Furbetta, Niccolò (Laparoscopic Surgery, 2018)
We read with particular interest the article entitled “Laparoscopic versus open repair of perforated peptic ulcer: A retrospective cohort study” (1).